Don't throw away: notes on the West Coast house - Liu, Charissa Hui Ying (Nanyang Technological University, 2024)
‘Don’t Throw Away: Notes On The West Coast House’ is a visual narrative and autobiography that aims to explore creative ways of using inanimate objects to tell immersive narratives. Drawing influence from ‘The Cultural Biography Of Things’ and conducting ‘Object Biographies’ (Kopytoff, 1986), this project looks at the objects in my multigenerational home as ‘living’ and ‘active’ devices of family history, memory and meaning. Through the collection of biographical information surrounding the objects in my home, this project experiments with the variety of ways inanimate objects can be used to visually convey narrative setting, plot, character, emotion, conflict, and theme. This project also explores the use of ‘The Book’ and its format as an active narrative object in creating immersive experiences of storytelling and visual communications.